A chemoselective fluorescent probe for arginine in aqueous phase. (July 2022) - Yu, Xianzhe; Zhang, Binjie; Liao, Peng; Huang, Jiarong; Fan, Cailing; Hu, Hui; Dong, Qinxi; Du, Gengyu; Gao, Yanan; Zeng, Chaoyuan
Abstract: As an essential amino acid, arginine (Arg) is of many biological significances. However, the chemoselective detection of Arg using fluorescent techniques remain challenging. Here, a 1, 1′-bi-2-naphthol (BINOL)-based fluorescent probe has been synthesized and responds chemoselectively to Arg to give strong fluorescence enhancement within a minute. The probe can report the concentration of Arg in a large window from 10 μM to 5 mM. UV irradiation provides a qualitative method for Arg detection. The fluorescence of the formed imine product can be turned off again by either acid or base. Based on those findings, a simple fluorescence OFF-ON-OFF device has been made for the fast detection of Arg. Highlights: Chemoselective detection of arginine among all amino acids. Colorimetric detection for qualitative detection. Fast detection (60 s vs. hours in other work). Large detection window (0–500 eq. of arginine vs tens of eq. in other work). Fluorescence OFF-ON-OFF mechanism and a simple device.